Pengaruh Kualitas Informasi, PersepsiKebermanfaatan, Kemampuan Individual Dan NormaSubyektif Terhadap Minat Mahasiswa DalamMenggunakan Internet Sebagai Sumber Pustaka( Survei Pada Mahasiswa Akuntansi Ums Dan Uns) - Hastuti, Heni Puji; , Dr. Fatchan Achyani, M.Si (2017)
This research aims to analyze the influence of the quality of information, perceived usefulness, the ability of the individual and subjective norms on student interest in using the internet as a source of literature on accounting students in UMS and UNS. The data used were taken from 85 questionnaires were distributed to students S1 Accounting Faculty of Economics and Business, University of Muhammadiyah Surakarta and University of March Surakarta with convenience sampling method. Data analysis techniques using multiple regression. The result indicatethat the quality of information significantly influence the student's interest in using the internet as a source of literature, perceived usefulness significantly influence the student's interest in using the internet as a source of literature, individual capabilities significantly influence the student's interest in using the internet as a source of literature, and subjective norms significant effect on student interest in using the internet as a source of literature.